DETERMINAN VARIABEL INFLASI DAN NILAI TUKAR TEHADAP PEMBIAYAAN PERBANKAN SYARIAH DENGAN PERTUMBUHAN EKONOMI SEBAGAI VARIABEL MODERATING - admin; Arifa Pratami (Wahana Islamika: Jurnal Studi Keislaman, 2018)
The purpose of this study is to analyze the determination of inflation and exchange rates on the financing of Islamic banking with economic growth as a moderating variable. This study uses secondary data taken entirely from official sources in monthly form starting from January 2010 to December 2017. Data sources for Non Performing Financing (NPF), Third Party Funds (TPF) and financing are obtained from Bank Indonesia Sharia Banking Statistics ( SPS-BI) and Statistics on Islamic Banking of the Financial Services Authority (SPBS / OJK). Sources of inflation data and exchange rates are obtained from BI's official website (www.bi.go.id), and the Industrial Production index (IPI) data source as a proxy for economic condition data accessed from the official BPS website (www.bps.go.id) . The results of the study found that inflation had a positive but not significant effect on financing channeled by Islamic banking, the rupiah exchange rate had a negative and significant influence on the financing of Islamic banking. Economic growth is not able to moderate the relationship between inflation and financing of Islamic banking, economic growth is able to moderate the relationship between exchange rates on Islamic banking financing.